2015
DOI: 10.1002/vnl.21516
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mechanical, fire‐retarding, and morphological properties of high‐density polyethylene/(wood flour) composites with different flame retardants

Abstract: Aluminum hydroxide, magnesium hydroxide, and 1,2-bis(-pentabromophenyl) ethane were incorporated into highdensity polyethylene (HDPE) and wood flour composites, and their mechanical properties, morphology, and fireretardancy performance were characterized. The addition of flame retardants slightly reduced the modulus of elasticity and modulus of rupture of composites. Morphology characterization showed reduced interfacial adhesion among wood flour, HDPE, and flame retardants in the composites compared with con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…[266] The HDPE wood flour composites with 10 wt% 1,2-bis(pentabromophenyl) ethane had great fire execution as it advanced the arrangement of consistent and compacted roast layer on the composite surface, which went about as an effective actual boundary to burning of composites. [267] The varying temperatures at which cellulose decomposes range between 200 and 350 C. The residual recovered after decomposition consists of flammable volatiles and gasses, non-combustible gasses, tars, and some char. [266] Similarly, the decomposition of the hemicellulose takes place at a range of temperature between 200 and 260 C, and residuals of this is non-combustible gasses and tar, which are less than cellulose.…”
Section: Flammability Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[266] The HDPE wood flour composites with 10 wt% 1,2-bis(pentabromophenyl) ethane had great fire execution as it advanced the arrangement of consistent and compacted roast layer on the composite surface, which went about as an effective actual boundary to burning of composites. [267] The varying temperatures at which cellulose decomposes range between 200 and 350 C. The residual recovered after decomposition consists of flammable volatiles and gasses, non-combustible gasses, tars, and some char. [266] Similarly, the decomposition of the hemicellulose takes place at a range of temperature between 200 and 260 C, and residuals of this is non-combustible gasses and tar, which are less than cellulose.…”
Section: Flammability Propertiesmentioning
confidence: 99%
“…[ 266 ] Similarly, the decomposition of the hemicellulose takes place at a range of temperature between 200 and 260°C, and residuals of this is non‐combustible gasses and tar, which are less than cellulose. [ 267 ] Then lignin decomposition takes place at 160 and 400°C that is basically because of the differing bonding condition. Lignin has a greater influence on the degradation of cellulose.…”
Section: Evaluation Of Natural Fiber Composites Characteristicsmentioning
confidence: 99%
“…Stark et al and Sain et al reported positive effects with magnesium hydroxide (MH), whereas no benefit regarding the use of aluminum hydroxide (ATH) was indicated by Arao et al . Zhang et al compared the effectiveness of ATH, MH, and 1,2‐bis(‐pentabromophenyl) ethane in HDPE‐based WPC and concluded that the latter FR exhibited the best fire resistance.…”
Section: Introductionmentioning
confidence: 99%